IMPLEMENTASI METODE PEMBELAJARAN BAHASA MANDARIN PADA MATA KULIAH MIKRO TEACHING - Ina, Ina; Patriantoro, Patriantoro (Jurnal Visi Ilmu Pendidikan, 2024)
Abstract"Micro Teaching" is a mandatory course in the Mandarin Language Education Program at the Faculty of Teacher Training and Education (FKIP), Tanjungpura University, serving as preparation for students before their Practicum in Schools (PPL). The primary focus of this course is to provide students with an opportunity to apply the theoretical teaching skills they have previously learned. This descriptive study, using observation, surveys, and interviews, reveals that in teaching vocabulary, grammar, and reading, instructors in micro-teaching tend to rely on the translation method. There is also the utilization of visual aids, either separately or in combination with other methods, although instructors have not fully implemented them effectively in the classroom. The dominance of the translation method in the learning process is due to its simplicity and speed, especially considering the limitations in Mandarin language proficiency among instructors. Unfortunately, the teaching of pronounciation and Hanzi tends to be neglected, focusing solely on the sequence of writing Hanzi characters. Moreover, the interaction pattern between teachers and students, which should ideally be two-way and practical, still tends to be dominated by the role of the teacher.Keywords: Micro-teaching, Teaching Method, Chinese.  Abstrak  "Micro Teaching" merupakan mata kuliah wajib di Prodi Pendidikan Bahasa Mandarin FKIP Universitas Tanjungpura, sebagai persiapan bagi mahasiswa sebelum menjalani PPL di sekolah. Fokus utama mata kuliah ini adalah memberikan kesempatan kepada mahasiswa untuk menerapkan teori keterampilan mengajar yang telah dipelajari sebelumnya. Penelitian deskriptif ini dilakukan melalui metode observasi, survei, dan wawancara, dengan hasil bahwa dalam pengajaran kosakata, tata bahasa, dan bacaan, guru-guru dalam micro teaching cenderung mengandalkan metode penerjemahan. Terdapat juga penggunaan metode gambar dan ilustrasi, baik secara terpisah maupun kombinasi dengan metode lainnya, namun guru belum sepenuhnya mampu mengimplementasikannya dengan baik di kelas. Metode penerjemahan lebih dominan dalam proses pembelajaran dikarenakan kemudahannya dan kecepatannya, terlebih lagi karena adanya keterbatasan kemahiran guru dalam berbahasa Mandarin. Sayangnya, pembelajaran pelafalan dan Hanzi cenderung terabaikan karena hanya fokus pada urutan penulisan karakter Hanzi. Selain itu, pola interaksi antara guru dan siswa, yang seharusnya bersifat dua arah dan efektif, masih cenderung didominasi oleh peran guru.  Kata Kunci: Micro teaching, Metode Pembelajaran, bahasa Mandarin.